Effects of Ag Addition on Precipitation and Fatigue Crack Propagation Behavior of a Medium-Strength Al–Zn–Mg Alloy. Issue 3 (March 2018) - Lin, Lianghua; Liu, Zhiyi; Liu, Wenjuan; Zhou, Yaru; Huang, Tiantian
Abstract : Effects of trace addition of Ag on the fatigue crack propagation behavior and microstructure of a medium-strength aged Al–Zn–Mg alloy were investigated in the present work. The results show that a combination of enhanced tensile strength and improved fatigue crack propagation resistance in Al–Zn–Mg alloys is achieved with small addition of Ag. The enhanced strength is attributed to the high density of η′ precipitates within the grains and narrow precipitate free zones in the vicinity of grain boundaries. The main contribution to the improvement of fatigue crack propagation resistance comes from the coarser precipitates within the grains. When subjected to two-step aging, Ag-added alloy shows larger semi-coherent matrix precipitates. These relatively coarser precipitates increase the homogeneity of deformation and therefore improve the fatigue crack propagation resistance. In addition, microstructure analysis indicates that the size and distribution of inclusions as well as the grain structures of Al–Zn–Mg alloys are independent of Ag addition.